4x +y = 16 ;2x + 3y = 24 Multiply the 2nd with -2, that gives -4x -6y = -48 Add the two: 0x - 5y = -32
Division by -5 gives y = 6,4
Insert this value into the first equation: 4x + 6,4 = 16
4x = 9,6 ; x = 2,4
Number 2 is even easier:
Multiply the first equation by 2 and add the equations.
24x + 2y = 50 plus 8x - 2y = 14 gives 32x = 64; x = 2
You can now choose: 24 + y = 25 or 16 - 2y = 14
(That you get when you replace in the original equations
x by 2) Anyhow you'll find y = 1
2006-11-17 07:52:21
·
answer #1
·
answered by corleone 6
·
0⤊
0⤋
Confirming the first answer.
1. Transfrom first equation y=16-4x. Fit into second equation: 2x+3*(16-4x)=24 -> 2x+48-12x=24 -> -10x=-24 ->x=2.4. Then y=16-4*2.4=6.4
So x=2.4, y=6.4.
2. Similar to 1.:
y=4x-7. Entered in first equation: 12x+4x-7=25 -> 16x=32 ->x=2; y=4*2-7=1
So x=2, y=1
2006-11-17 15:49:50
·
answer #2
·
answered by Chris 4
·
0⤊
0⤋
Solve by using system of equations. For number one, multiply the first equation by -3 so that the Y's will cancel out and you can solve for X. Plug in your answer for X into one of the equations and solve for Y. X = 2.4 and Y = 6.4
For number similar. Multiply the first equation by 2 so you can cancel out the y's and get a value for X. Subsitute your X value into one of the equations and you should get your Y value. X=2 and Y = 1
2006-11-17 15:51:20
·
answer #3
·
answered by sophi p 2
·
0⤊
0⤋
1. 4X + Y = 16 ; 2X + 3Y = 24
multiply first equation by three;
=>12x+3y=48
subtract one from the other to get;
10x=24
x=2.4
put that into one of the above and rearrange for y to get y=6.4
2. 12X + Y = 25 ; 8X - 2Y = 14
multiply first on by 2;
=>24x+2y=50
add to the other one to get;
32x=36
so x=1.125
and put x into one of the above to get y by rearrangment again;
I get y=-11.5
2006-11-17 15:49:09
·
answer #4
·
answered by jj 2
·
0⤊
2⤋
1. x = 2.4 , y = 6.4
2. x = 2 , y = 1
2006-11-17 15:39:00
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋